APLIKASI PENELUSURAN KERUSAKAN BLACKBERRY BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract - The development of current computer technology plays an important role in improving the performance so as to produce better results with a faster time. One application in the field of communications applications to diagnose damage blackberry is one of the applications of computer science development. Damage to the blackberry app builds upon the problem because users generally still very common with damage problems that occur on blackberries they use . Blackberry application development searches breakdown built based on the method of data collection methodology and system development. Methods of data collection in the form of library research and interviews. System development method based on principal component analysis of the needs of the system , namely, knowledge representation, inference engines, database design, system design, system implementation and a case example. This application uses forward chaining inference method ( forward tracking ) is a graph penelurusan blackberry. So in search of damage that is a fact - a fact that is entered by the user, with the rules that have been stored in the system then the conclusion can be drawn that the damage blackberry. The blackberry tracking application malfunction can support two users are experts and general users. Experts can enter, modify and delete knowledge base, rules and blackberry browsing damage. Common user can only perform searches blackberry damage.Keywords – Expert System, Forward Chaining, Blackberry, Framework.